Experimental Study on the Stabilization of Soil by Using Plastic Wastes - Saravanaganesh, S.; Priyanka, R.; Sinduja, S.; Balakumar, K.; Chellaiah, A. (International Journal of Scientific Research in Civil Engineering, 2016)
The road pavements and sub-grades are severely affected during the rainy season, which results in the failure of the road. The rain water will penetrate the surface of the sub grade and weaken their stability. It will also result in heave frosting. To prevent the road from failure, the nature of the onsite materials are improved along with their stability by the process of stabilization. Many roads agencies have been experiencing problem of premature failure of pavements like potholes, roughness, cracks etc. which leads to poor performance of roads and its life. On the other hand, plastics, rubbers, etc. are increasing day by day. There are many ground improvement techniques to improve the strength of the soil. One of them was Stabilization of the soil by using plastic wastes. India nearly pumps 0.6 million tons of plastic per year. According to central pollution control board [CPCB] the plastic wastes generated will be about 15,342.6 tonnes per day. These plastic wastes cause a great harm to the environment and their surroundings. So it is very important to dispose of these wastes. The disposal of these wastes by the stabilization technique was cost effective and economical. This paper presents the stabilization of the sub grade soil by using plastic granules made from the plastic wastes. The plastic materials used for the stabilization are made by recycling the polypropylene plastic bags. Soil acts as a reinforcing material and resists the entry of water when mixed with varying proportions of plastic granules. As a result when the percentage of plastic increases, then the strength of the soil also gets increased with increase in plastic content.